Pengaruh Pembayaran Non Tunai dan Tunai terhadap keuangan UMKM Makanan dan Minuman di Kecamatan Sedati Sidoarjo - Putra, Firmansyah (Research Journal of Social Science and Economics, 2025)
Small and Medium Enterprises (MSMEs) as one of the elements of economic growth occupy a strategic position to accelerate structural changes in order to improve the people's standard of living. In the current development of globalization, MSME actors must keep up with changes with the existence of a payment system in the form of Non-Cash and Cash. The payment system is an important component in MSME finance and is also one of the performance programs of Bank Indonesia as the Central Bank in improving the payment system in order to achieve better economic growth. This type of research is quantitative research with the aim of this study to find out how much effect non-cash payments and cash payments have on MSME finances, especially in the Sedati sub-district, by collecting data through questionnaires distributed to 117 MSME actors who have met the income criteria from the technical analysis business sector data with multiple regression analysis also used hypothesis testing, namely partial t test, simultaneous F test of determination efficiency. This study found that non-cash variables on MSME finance showed a positive and significant effect on MSME in Sedati District. Based on statistical calculations, it is known that the tcount value is greater than t-table, so it means that Ha is accepted while H0 is rejected, so non-cash payments have an effect on the MSME economy in Sedati Regency. Proving financial variables, t-count is greater than t-table, then Ha is accepted while H0 is rejected, so that cash payments have an effect on MSME financing in Sedati District. Keywords: non-cash payments, cash payments, MSME finance